IMPLEMENTASI CROWDFUNDING UNTUK PENGEMBANGAN SISTEM INFORMASI STARTUP BERBASIS ANDROID - Akhmad Budi, S.Kom., MM., M.Kom (Jurnal Informatika dan Bisnis, 2018)
As more and more levels of the technology that can help us on any side, we must use this advantage as good as possible. In the other side, many startup compete each other to get funding and attention from the people. For that reason, it may be helpful if we have an application which can be a media to get a funding and publish for a startup. To establish an investment information system, authors use a variety of theories that are used as a reference. The application was developed with Android based programming language Java that can be easily accessed and executed through the Internet. In this research, data collection is done by doing an observation of some crowdfunding websites. The development of systems have been done using object-oriented analysis and design that can be described by the Unified Modelling Language (UML). Results from this research is a crowdfunding application that can be used by anyone, especially for those who have an idea or startup to get funding or for them who have capability to fund a project. The conclusion of this research is the crowdfunding application can be used as a media to publish a project and get funding, so it can make get the funding much easier and increasing the level of competitiveness that can create a good competition.Keywords: Android, Information System, Crowdfunding, funding, investment, technology